Did I find the right examples for you? yes no

# numpy.polynomial.hermite_e.hermemulx

All Samples(6)  |  Call(6)  |  Derive(0)  |  Import(0)
```Multiply a Hermite series by x.

Multiply the Hermite series `c` by x, where x is the independent
variable.

Parameters
----------
c : array_like
1-D array of Hermite series coefficients ordered from low to(more...)
```

```        def hermemulx(c):
"""Multiply a Hermite series by x.

Multiply the Hermite series `c` by x, where x is the independent
variable.

Parameters
----------
c : array_like
1-D array of Hermite series coefficients ordered from low to
high.

Returns
-------
out : ndarray
Array representing the result of the multiplication.

Notes
-----
The multiplication uses the recursion relationship for Hermite
polynomials in the form

.. math::

xP_i(x) = (P_{i + 1}(x) + iP_{i - 1}(x)))

Examples
--------
>>> from numpy.polynomial.hermite_e import hermemulx
>>> hermemulx([1, 2, 3])
array([ 2.,  7.,  2.,  3.])

"""
# c is a trimmed copy
[c] = pu.as_series([c])
# The zero series needs special treatment
if len(c) == 1 and c[0] == 0:
return c

prd = np.empty(len(c) + 1, dtype=c.dtype)
prd[0] = c[0]*0
prd[1] = c[0]
for i in range(1, len(c)):
prd[i + 1] = c[i]
prd[i - 1] += c[i]*i
return prd
```

```    def test_hermemulx(self):
assert_equal(herme.hermemulx([0]), [0])
assert_equal(herme.hermemulx([1]), [0,1])
for i in range(1, 5):
ser = [0]*i + [1]
tgt = [0]*(i - 1) + [i, 0, 1]
assert_equal(herme.hermemulx(ser), tgt)
```

```    def test_hermemulx(self):